THE INFLUENCE OF PERCEIVED ECONOMIC BENEFITS, SUBJECTIVE NORMS, AND MORAL OBLIGATION TOWARDS INTENTION TO PIRATE SVOD PRODUCTS IN INDONESIA - Chiara Dyani Hatti; Yohanes Thianika Budiarsa (Interaksi Online, 2026)
The rapid expansion of Subscription Video-on-Demand (SVoD) platforms alters entertainment consumption patterns throughout Indonesia. Digital piracy remains deeply widespread despite the extensive availability of official streaming channels. This quantitative explanatory study inspects how perceived economic benefits, subjective norms, and moral obligations dictate individual intentions regarding SVoD product piracy. An online questionnaire gathered data from 246 qualified respondents before evaluation via Partial Least Squares Structural Equation Modeling (PLS-SEM). Empirical results demonstrate that perceived economic advantages exert no significant influence on piracy intentions (? = 0.480; ? = −0.003). Subjective norms directly stimulate unauthorized downloading inclinations with a positive significant impact (? = 0.012; ? = 0.142). Moral obligation generates an unexpected positive significant path coefficient opposing the original hypothesis (? = 0.000; ? = 0.638). Piracy tendencies depend heavily upon peer dynamics and localized ethical rationalizations rather than direct cost considerations.